2022
DOI: 10.1371/journal.pgph.0000131
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked and unaddressed: A narrative review of mental health consequences of child marriages

Abstract: Child Marriage (before the age of 18) affects over 12 million young women globally, annually. Despite acknowledgement of the negative impacts of the practice on reproductive health, mental health consequences are largely overlooked. Given the ability for poor mental health to intensify other health and social challenges, understanding the mental health consequences linked to child marriage is vital. Our study is the first to examine how mental health is approached in current literature on child marriage. Our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Also, younger girls have a stronger emotional attachment to their own families, which may make the transition more difficult and impact on relations with their in‐laws (Moretti & Peled, 2004; Palriwala, 1993). While large studies on the emotional consequences of child marriage are lacking, there is increasing evidence that adolescents marrying young experience negative mental health consequences (Burgess et al, 2021; Kidman, 2017; Kumar et al, 2018; Oshiro et al, 2011; Raj et al, 2018; Sezgin & Punamäki, 2020). However, the differences in social and cultural contexts between studies limits comparison, and research on the mental health consequences of child marriage in Nepal is limited (Chaulagain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, younger girls have a stronger emotional attachment to their own families, which may make the transition more difficult and impact on relations with their in‐laws (Moretti & Peled, 2004; Palriwala, 1993). While large studies on the emotional consequences of child marriage are lacking, there is increasing evidence that adolescents marrying young experience negative mental health consequences (Burgess et al, 2021; Kidman, 2017; Kumar et al, 2018; Oshiro et al, 2011; Raj et al, 2018; Sezgin & Punamäki, 2020). However, the differences in social and cultural contexts between studies limits comparison, and research on the mental health consequences of child marriage in Nepal is limited (Chaulagain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For all the potential advantages of school-based programmes (accessibility, scalability, and efficacy), they usually exclude adolescents who are not in education. In Nepal this is around 12% of adolescents who tend to be from poorer households, are at greater risk of early marriage and child labour and are likely to have more mental health problems than school-going adolescents (Burgess et al ., 2022 ). Although we did not explicitly exclude out of school adolescents, we did not proactively search for them.…”
Section: Discussionmentioning
confidence: 99%
“…With such a definition, the emphasis is on the importance of functionality in one's life, which moves beyond the presence or absence of a mental disorder. While there is a wide range of tools that focus on the diagnosis of disease, fewer tools exist that attempt to grapple with the positive dimensions of mental health, focusing on the capacity and overall wellbeing [23,[38][39][40]. Even fewer have been widely used in sub-Saharan Africa [41,42].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…A study by Akinyemi et al [2016] found the risk of death in childhood was 23% higher in extended family households compared to nuclear family households [15]. Early marriage also remains a common practice in Northern Nigeria [21,22] and has clear relationships to poor mental health outcomes [23]. Given gendered roles within part of our co-design process.…”
Section: Introductionmentioning
confidence: 99%